The Results of the SWOT Analysis Approach in Formulating Company Strategy at the American English Course Purwokerto - Mayla Surveyandini (ProBisnis : Jurnal Manajemen, 2022)
This research is entitled "The results of the SWOT analysis approach in formulating company strategy at the american english course purwokerto". The purpose of this study is to determine and measure the company's strengths (Strength), company weaknesses (Weakness), analyze opportunities (Opportunities) and threats (Threats) at the American English Course Purwokerto. This research is a descriptive qualitative research by collecting information about research subjects and the behavior of research subjects in a certain period. Data processing is carried out with a SWOT analysis process as a strategy formulation tool. The SWOT analysis that has been formed is then formulated in the form of a SWOT matrix with 4 (four) strategic formulas, namely SO Strategy, WO Strategy, ST Strategy and WT Strategy. The results of the study show that the American English Course is a business engaged in services. An effective and optimal planning strategy is needed that covers all aspects from planning to marketing. Quality products, optimal services supported by the right infrastructure including promotional activities will certainly bring success to the company's progress. Customer satisfaction is the key that must be prioritized to seize market share that is increasingly growing and competitive. The findings in this study have several important implications for the company to further improve and improve strategies both in terms of planning and marketing, namely the need to improve product quality and human resources, improve service and creativity to consumers so that consumers do not move to other competitors, use technological developments as learning and promotion facilities.